Full and open competition in public procurement: a noble lie. (27th April 2023) - Atkinson, Christopher L.; McCue, Clifford; Prier, Eric
The notion that the US federal government provides equal opportunity for all businesses to potentially receive contracts may be, as discussed in Plato's Republic, a noble lie. In this context, the noble lie represents government's attempt to advance an agenda that is ostensibly in the public interest yet is empirically untrue. Using the 'full and open competition' designation and number of offers as a measure of actual competition for government contracts, this research shows that competitive contracting by the US federal government is more an ideal than actual practice. Based on these findings, it is asserted that full and open competition is consistent with a noble lie, existing as an ideal not regularly attained, but nonetheless offered in service of other ends. Contextualising and linking the noble lie with trust signals areas for future research regarding competition in public procurement.